Development and validation of an HPLC/DAD method for the determination of 13 sulphonamides in eggs. (15th November 2015) - Summa, Simona; Lo Magro, Sonia; Armentano, Antonio; Muscarella, Marilena
Highlights: Accurate and selective multiresidue HPLC/DAD method for determination of 13 sulphonamides in eggs. Sensitivity comparable to that of MS methods without the use of sophisticated and expensive systems. Method validation protocol according to the Decision 2002/657/CE. Abstract: A simple, sensitive and selective multiresidue high-performance liquid chromatography with diode array detection method for determination of 13 sulphonamides in eggs was developed and validated. Sample extraction and clean-up conditions were carefully studied and factors as gradient elution and column temperature were found as key parameters to improve separation efficiency. The method was validated following the European Commission Decision 2002/657/EC criteria adopting spiking levels of 20, 40 and 60 μg kg −1 "As Low As Reasonably Achievable". The necessary requirements for precision (RSDR % below 23%) and trueness (recovery ranging from 45.2% to 87.5%) were fulfilled. Decision limit (CCα) values below 18.5 μg kg −1, comparable to those reported in LC-MS detection, demonstrated the suitability of the method in residues surveillance plans for the sulphonamides analysis in eggs at the carry-over level without the use of sophisticated and expensive instrumentation.